It's time to change how we think about our employees. Issue 2 (20th May 2021) - Martin, Jim
Abstract : Purpose: This paper aims to propose the need to be bolder about recognizing when an employee needs to be let go. Design/methodology/approach: This paper is based upon a review of literature and extensive fieldwork. Findings: Three situations are presented for when releasing an employee may be the appropriate tactic, along with five general principles for shifting the organization–employee relationship from unhealthy enmeshment to a mutually beneficial arrangement. Originality/value: This paper proposes a practical view of the organization–employee relationship that strives to enhance organizational performance while honoring the humanity of the employee.